Edukasi Recycle Craft untuk Lingkungan Bersih Kreatif pada Siswa SD Muhammadiyah 7 Palembang - Zairinayati, Zairinayati; Anggraini, Rahma Dwi; Fitria, Shabiya (Jurnal Nusantara Mengabdi, 2024)
Purpose: This activity aims to raise awareness among students, teachers, and the school community about waste management, develop student creativity through crafts made from recycled materials, and encourage the habit of sorting waste and reusing inorganic waste. Methodology/approach: The activity was conducted through lectures, demonstrations of making crafts from inorganic waste, and a Q&A session with door prizes. Participants were taught how to make flowers from single-use plastic cups. The activity was attended by 20 students from grades 3 and 6 of SD Muhammadiyah 7 Palembang. Results/findings: Participants understood the steps in making crafts from plastic cups. This program should be continued to help maintain the cleanliness of the school environment. Conclusion: This program contributed to the school's efforts in maintaining cleanliness from plastic waste. Limitation: This activity only involved 20 students, so its impact has not yet been widely felt. Moreover, the focus is still on education and crafting, without a long-term strategy for program sustainability. However, this program has effectively raised awareness of waste management and recycling creativity at SD Muhammadiyah 7 Palembang.